Aplicación del proceso de atención de enfermería a un RN con hiperbilirrubinemia hospitalizado en el área de CIN en el Hospital Guasmo Sur. - Suarez Verdezoto, Gardenia Yulexy (2019)
The present work was carried out in the General Hospital Guasmo Sur with the aim of developing a nursing care plan, the development of this work was carried out by directing it to a newborn with hyperbilirubinemia, since babies who have jaundice in the first days are between 60-70%; This pathology appears when bilirubin accumulates in the baby's blood because the liver is not able to process it normally, it manifests itself through yellowing of the eyes, sclera and mucous membranes. The development of this case study has allowed us to observe and understand the evolution of the newborn, although not everyone reacts in the same way, an effective recovery process could be contemplated, this was due to the timely action of the medical team and also of Baby's parents The risk of complications due to this cause is greater the more premature the newborn is. This case has been followed up to solve the problem by improving the quality of life of the newborn. It is one of the situations that most worries parents, so it is essential to educate them about their baby's illness and how they should act in this case.